ANALISIS PENERAPAN PERMENDAGRI NO.113 TAHUN 2014 DALAM PERENCANAAN, PELAKSANAAN DAN PERTANGGUNGJAWABAN APBDes (STUDI KASUS DESA MOTANDOI DAN MOTANDOI SELATAN KECAMATAN PINOLOSIAN TIMUR KABUPATEN BOLAANG MONGONDOW SELATAN) - Kadjudju, Delyane; Morasa, Jenny; Lambey, Robert (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
Village is a unity of the general public that has territorial boundaries authorized to regulate and administer government affairs, the interestsof local communities based on community initiatives, right of origins/ or traditional rights recognized in the governance system of the The Unitary State of the Republic of Indonesia. Financial management of village is all activities that includes planning, implementation, administration, reporting, and financial accountability village. APBDes is the annual financial plan of village government. This research aimed to know planning, implementation, and accounibility village financial management in Motandoi and South Motandoi  village, subdistrict East Pinolosian, South Bolaang Mongondow. The method used is descriptive qualitative. The result of the research  Motandoi village in planning and implementation phase already approriate with Permendagri number 113 of  2014, but in accountability phase not yet approriate with Permendagri number 113 of  2014, while South Motandoi Village on planning, implementation, and accountability phase already approriate with Permendagri number 113 of 2014. Keywords: Village, Planning, Implementation, Accountability, financial management of Village.